The financial accounting system and the difficulties of its application as well as measures for its improvement - Nebeg , Kouider; Djekidel , Yahia; Boudjelal , Ahmed (Finance and Business Economies Review, 2021)
This study aims to highlight the constraints that have contributed to the unsuitability of the financial accounting system to the Algerian economic, social and cultural environment due to the fact that this system based strongly on international accounting standards IAS / IFRS constitutes an advance compared to to the Algerian economy deprived of a financial market and to the culture of professionals and salaried accountants reluctant to any change in view of the lack of communication and the outdated reflexes of the patrimonial approach enshrined in law and do not allow any multi-criteria approach. This study also aims to propose useful solutions that the Algerian state must consider in order to remedy the paradoxical situations (biased environment, unsuitable training, deregulated market) in which the financial accounting system is found.